Enhanced Figure of Merit via Hybridized Guided‐Mode Resonances in 2D‐Metallic Photonic Crystal Slabs. Issue 21 (7th August 2022) - Sarkar, Swagato; Ghosh, Anik Kumar; Adnan, Mohammad; Aftenieva, Olha; Gupta, Vaibhav; Fery, Andreas; Joseph, Joby; König, Tobias A. F.
Abstract: Metallic nanostructures are highly attractive for refractive index sensing, as the evanescent field from the associated plasmonic resonances resides in close proximity to the adjacent analyte media. However, this benefit is often reduced due to broad plasmonic lineshapes producing poor quality factors. The rational design provides strategies for narrowing the plasmonic modes by incorporating photonic diffraction, which promotes surface lattice resonances . Due to the stringent parametric dependencies, these resonances in metallic lattices are not always feasible, particularly when a straightforward fabrication route with fewer process steps is desired. Herein, hybridized guided‐mode resonance in a 2D‐metallic photonic crystal slab (2D‐mPhCs) is introduced that ensures high‐quality hybrid modes while maintaining a simple fabrication methodology. In direct comparison to its constituent plasmonic and photonic modes, this concept is discussed for sensing applications. The "figure of merit (FOM)" is frequently regarded as a valid metric for measuring sensing performanceensuring high‐quality modes with an improved detection limit. The experimental results confirm enhanced FOM (three to six times) for the hybrid modes, in contrast to the constituent counterparts. For optoelectronic applications, such as photodetection and photocatalysis, these hybrid structures with high‐quality modes offer a promising platform to harvest light at the metal–semiconductor interfaces. Abstract : 2D‐metallic photonic crystal slab (2D‐mPhCs) comprised of platinum nanodisc array and titania (TiO2 ) waveguide are explored to instigate plasmonic–photonic hybrid modes. Apart from theoretical modeling, experimental realization of the proposed structure is carried over a large area to easily implement the hybrid modes in sensing application, showing enhanced "figure of merit (FOM)" over its conventional photonic and plasmonic counterparts.